SAT0270 The Outcomes of Surgical and Percutaneous Vascular Intervention for Takayasu Arteritis in South Korea. (10th June 2014) - Moon, J.; Park, J.K.; Choi, I.A.; Lee, E.Y.; Song, Y.W.; Lee, E.B.
Abstract : Background: Takayasu arteritis (TA) affects the aorta and its major branches. The damage to arterial wall by the chronic inflammation often results in vascular complications including aneurysm formation or luminal stenosis which can be benefited from vascular interventions. Objectives: The aim of this study was to investigate outcomes of surgical and percutaneous intervention and to identify factors associated with vascular restenosis requiring a reintervention. Methods: In this retrospective study, patients with TA receiving care between 1979 and 2009 at Seoul National University Hospital were enrolled. Data on choice and outcome of vascular intervention were ascertained by medical chart review. Kaplan-Meier analysis and log-rank test were performed to compare the failure rate of surgical vs. percutaneous vascular interventions. Risk factors associated with a restenosis were investigated using cox proportional hazard regression analysis. Results: A total of 184 patients with TA were identified. The mean age at diagnosis was 35.3±16.4 years and 160 (87.2%) were female. Forty-four (23.9%) patients underwent open surgery and 25 (13.6%) patients underwent a percutaneous endovascular intervention. After median follow-up of 20.1±1.4 years, 17 (38.6%) patients in the open surgery group and 11 (44%) patients in the percutaneous intervention group developed significant restenosis requiring a second intervention (Fig. 1 ). The use of corticosteroid, azathioprine or cyclophosphamide did not affect restenosis rate (HR=0.77, 95% CI: 0.3–2.0). Nor did disease activity or traditional cardiovascular risk factors such as diabetes and hypertension (P>0.05). However, use of methotrexate was associated with a higher risk of significant restenosis (HR=2.48, 95% CI 1.074–5.747). Conclusions: Open surgical and percutaneous endovascular interventions for vascular complications in patients with TA did not differ in regard to the restenosis rate. Since treatment with methotrexate is associated with a higher restenosis rate, its use should be re-evaluated in a further study. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3983